Distribution of extensively drug-resistant Gram-negative bacteria, their antibiotic susceptibility profile, and the detection of metallo-β-lactamase production by them from a tertiary care center in New Delhi, India - Sarjana Shuchi; Shweta Satija; Manoj B Jais (Asian Journal of Medical Sciences, 2025)
Background: Metallo-β-lactamase (MBL) is becoming a bigger concern worldwide because of its ability to hydrolyze carbapenems which are the drug of choice for treating severe Gram-negative bacterial infections. Aims and Objectives: This study aimed to estimate the percentage positivity of different gram-negative bacterial isolates, their antibiotic resistance rate, the percentage positivity of MBL production by these isolates by phenotypic method and the samples contributing to them, and the demographic profile of the patients. Materials and Methods: It was conducted in the Department of Microbiology, Lady Hardinge Medical College, New Delhi from November 2022 to February 2023. Two hundred seven Gram-negative extensively drug-resistant (XDR) isolates were taken from various samples and their antibiotic susceptibility profile was noted. XDR bacteria resistant to imipenem were subjected to MBL detection by the combined disc test. Results: Most of the patients from whom these isolates were isolated were in the age group of >18–≤65 years. Out of 207 patients, 103 were admitted in intensive care unit while the patients admitted in the ward or who came to the outpatient department were 104. Acinetobacter baumannii with 65.21% was the major bacteria contributing to the XDR strains. Tetracycline group of drugs showed the maximum susceptibility among the tested antibiotics and all the isolates were intermediately susceptible to colistin. Out of 207 isolates, 197 were positive for MBL and A. baumannii among bacteria, and tracheal aspirate among the samples was the major contributor. Conclusion: Most of the isolates were positive for MBL, suggesting Gram-negative carbapenem-resistant XDR isolate could be considered positive for MBL if a detection facility is not available at the center.